Dynamics of Social Enterprises—Shift from Social Innovation to Open Innovation. (November 2017) - Yun, Jinhyo Joseph; Park, KyungBae; Im, ChoongJae; Shin, ChangHwan; Zhao, Xiaofei
This article looks into dynamics of open social enterprises. We used several research methods—literature review, content analysis and case studies through intensive interviews via semi-structured questionnaire. First, we developed a research framework, expressed as the social open innovation dynamics model through literature reviews on social economy, sharing economy, collaborative innovation, open innovation and social enterprise. Second, we applied the model to ten Korean social enterprises and determined the success factors of social open innovation, as well as the concrete dynamics behind it. Main finding of this research are as follows. The success of social enterprises depends on the extent to which they strive to move towards open innovation. Adopting open innovation strategies seem to be a fruitful pathway for social enterprises to progress and grow in their operations.